Recent Advances in Genetic Tools for Acinetobacter baumannii - Sykes, Ellen M. E.; Deo, Soumya; Kumar, Ayush (Frontiers in Genetics, 2020)
Acinetobacter baumannii is classified as a top priority pathogen by the World Health Organization (WHO) because of its widespread resistance to all classes of antibiotics. This makes the need for understanding the mechanisms of resistance and virulence critical. Therefore, tools that allow genetic manipulations are vital to unravel the mechanisms of multidrug resistance (MDR) and virulence in A. baumannii. A host of current strategies are available for genetic manipulations of A. baumannii laboratory-strains, including ATCC®17978TM and ATCC®19606T, but depending on susceptibility profiles, these strategies may not be sufficient when targeting strains newly obtained from clinic, primarily due to the latter’s high resistance to antibiotics that are commonly used for selection during genetic manipulations. This review highlights the most recent methods for genetic manipulation of A. baumannii including CRISPR based approaches, transposon mutagenesis, homologous recombination strategies, reporter systems and complementation techniques with the spotlight on those that can be applied to MDR clinical isolates.